Growth and Mortality Models of Mozambique Tilapia (Oreochromis mossambicus; Peters, 1852) Wildly Enter Inside the Fish Farming Ponds in Tarakan City, North Kalimantan - Gazali Salim; Mujiyanto Mujiyanto; Yayuk Sugianti; Suryanti Suryanti; Zahidah Zahidah; Daud Nawir; Sitti Hartinah; Nurjanah Nurjanah; Rose Dewi; Rama Iranda; Mochamad Candra Wirawan Arief; Masayu Rahmia Anwar Putri; et al. (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract